Exploration of Acceptance Factors of Online Learning Platform: A Theory of Planned Behavior Perspective - Adi Dharma Putra; Addin Aditya; Arif Tirtana (LPPM POLITEKNIK LP3I BANDUNG, 2024)
E-learning is recognized as a form of education facilitated through the application of information and communication technologies. The successful implementation of e-learning is influenced by numerous factors. This research aims to identify the determinants of online learning platform acceptance through the lens of the Theory of Planned Behavior (TPB). The study focuses on three independent variables: attitudes, subjective norms, and perceived behavioral control. Positioned as explanatory research with a quantitative emphasis, data were gathered from active students who met specific criteria and were subsequently given access to an online questionnaire. The research sample was obtained through a purposive sampling method. This study employs multiple linear regression analysis, executed through computational means. The hypothesis testing results indicate that two hypotheses—subjective norms on intention and intention on behavior—have a positive and significant influence, suggesting that perceptions from one's social environment can significantly shape users' intentions to engage with online learning platforms. However, the remaining three hypotheses reveal a positive yet insignificant effect, indicating that the variables of behavior and attitude control do not significantly impact the use of online learning platforms. Collectively, the four variables account for only 43.7% of the behavioral outcomes, with the remaining 56.3% likely influenced by other factors beyond the scope of this research. E-learning dikenal sebagai bentuk pendidikan yang difasilitasi melalui penerapan teknologi informasi dan komunikasi. Keberhasilan implementasi e-learning dipengaruhi oleh banyak faktor. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor penentu penerimaan platform pembelajaran online melalui lensa Theory of Planned Behavior (TPB). Penelitian ini berfokus pada tiga variabel independen: sikap, norma subjektif, dan kontrol perilaku yang dirasakan. Diposisikan sebagai penelitian eksplanatori dengan penekanan kuantitatif, data dikumpulkan dari mahasiswa aktif yang memenuhi kriteria tertentu dan kemudian diberikan akses ke kuesioner online. Sampel penelitian diperoleh melalui metode purposive sampling. Penelitian ini menggunakan analisis regresi linier berganda, yang dilakukan dengan cara komputasi. Hasil pengujian hipotesis menunjukkan bahwa dua hipotesis - norma subjektif terhadap niat dan niat terhadap perilaku - memiliki pengaruh yang positif dan signifikan, yang menunjukkan bahwa persepsi dari lingkungan sosial seseorang dapat secara signifikan membentuk niat pengguna untuk terlibat dengan platform pembelajaran online. Namun, tiga hipotesis lainnya menunjukkan pengaruh yang positif namun tidak signifikan, mengindikasikan bahwa variabel perilaku dan kontrol sikap tidak secara signifikan mempengaruhi penggunaan platform pembelajaran online. Secara kolektif, keempat variabel tersebut hanya menjelaskan 43,7% dari hasil perilaku, dengan 56,3% sisanya kemungkinan dipengaruhi oleh faktor-faktor lain di luar cakupan penelitian ini.